Level of Knowledge about the Risk Factors of Breast Cancer in Local Population Presenting with Breast Lump - Ayesha Afridi, Saima Akbar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer is the most common form of organ-specific cancer in females. It is responsible for 26% of all cancers that are newly diagnosed in women and 15% of all cancer-related fatalities in females. Objective: To ass knowledge Level about the risk factors of Breast Cancer in local population presenting with breast lump Methodology: This study was descriptive cross-sectional done at the Surgery department of Khyber Teaching Hospital, Peshawar. The study was conducted for a period of one year from January 2011 to December 2012. All the information’s were documnted in the data collecting performa. Data was analyzed by SPSS version 14. Results: In the current study, totally 210 female patients were enrolled. Only 10.4% of patients had a good knowledge of the risk factors for BC, whereas 35.3% had moderate knowledge and 54.2% had a poor understanding. Less than 50% of women responded positively when asked about the other risk factors, but 54.22 percent of them recognized that using oral contraceptives or hormone replacement therapy increased the chance of BC. Conclusion: Among women, breast cancer has the highest incidence rate, and its prevalence is quickly increasing in low- and middle-income countries. According to this research, most of the risk factors for BC are unknown to the majority of women in our society. The high incidence of BC in our society is largely due to this lack of awareness of the risk factors. Keywords: Level of Knowledge; Breast cancer; Risk factors